Analysis Of The Implementation Of Profit And Loss Distribution Based On Capital Portion - Anni Safitri; Mar'atus Sholikah; Kresna Rahma Aji (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
This study examines the profit and loss sharing mechanism in CV Icons Indonesia based on the partnership agreement and the method of calculating the cost of goods manufactured (COGM). The research employs the job order costing method to determine the COGM of Denim Bags and Levis Bags in August 2025. According to the partnership agreement, where 100% of the capital is contributed by the wife as a passive partner, all partnership profits are allocated to her. The study highlights the importance of a clear partnership agreement in ensuring equitable profit distribution and the sustainability of the business.